The Taishan Robinia pseudoacacia polysaccharides enhance immune effects of rabbit haemorrhagic disease virus inactivated vaccines. (November 2017) - Yang, Shifa; Li, Guiming; Zhao, Zengcheng; Feng, Minyan; Fu, Jian; Huang, Zhongli; Song, Minxun; Lin, Shuqian
Abstract: Robinia pseudoacacia flower, a common component in traditional Chinese medicine, has long been well-known for its high pharmaceutical value. This study aimed to assess the immunopotentiating effects of Taishan Robinia Pseudoacacia polysaccharides (TRPPS) in rabbits inoculated with a rabbit haemorrhagic disease virus (RHDV) inactivated vaccine. The rabbits were administered with the RHDV vaccine in conjunction with varying concentrations of TRPPS, and their blood samples were collected at different time points to analyze the ratio and number of blood lymphocytes. In addition, sera were prepared and analyzed to determine the overall antibody titer and the level of IL-2, a cytokine commonly used as an indicator of immune activity. The various TRPPS-supplemented vaccines were shown to be more effective in enhancing the immune functions of the inoculated rabbits compared to their polysaccharide-free counterpart, with 200 mg/mL of TRPPS exhibiting the most pronounced benefits that were comparable to those of propolis. In addition, the TRPPS-supplemented RHDV inactivated vaccines could significantly improve the survival rates of the immunized rabbits against RHDV infection. Our studies offered convincing experimental evidence for the development of TRPPS as a new type of plant-derived immunopotentiator. Highlights: This study aimes to assess the immunopotentiating effects of TRPPS in rabbits inoculated with RHDV inactivated vaccine. TRPPS is effective in enhancing the immune functions of the inoculated rabbits. TRPPS-supplemented vaccines significantly improve the survival rates of the rabbits against RHDV infection. TRPPS is a new type of plant-derived immunopotentiator.